Symposium on Sidney Tarrow’s War, States, and Contention. An Introduction and brief thoughts on the 800th anniversary of Magna Carta - Parks, Louisa (PARTECIPAZIONE E CONFLITTO, 2015)
For Symposium abstract is not required